Factors of words with the modified semantic structure (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article is devoted to the factors of words altered semantic structure. In the history of words such changes can leave the dual track. On the one hand, a denotation can be characterized by several significatum that are united transfer part. On the other hand, the modified value may be the only linguistic reality that is fixed norm of the modern Russian language and lose the initial set of seeds as part sememe.
Keywords: semantic changes; denotation; significatum; inner form ofa word; semantic structure of a word